2011
DOI: 10.1186/1756-0500-4-519
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of hope and optimism with anxiety and depression in a specific group of cancer survivors: a preliminary study

Abstract: BackgroundAnxiety and depression have been identified as a common psychological distress faced by the majority of cancer patients. With the increasing number of cancer cases, increasing demands will be placed on health systems to address effective psychosocial care and therapy. The objective of this study was to assess the possible role of hope and optimism on anxiety and depression. We also wanted to investigate if there is a specific component of hope that could play a role in buffering anxiety and depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
5
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 29 publications
5
69
5
2
Order By: Relevance
“…The prevalence of depression is similar to the range found in previous literature review (HaisfieldWolfe et al, 2009). Findings in this study indicated more depression cases than obtained in an earlier study done in Hong Kong (Rajandram et al, 2011). Rajandram et al (2011) concluded that approximately 8% of the oral cancer study participants met the clinical cut-off for depression.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The prevalence of depression is similar to the range found in previous literature review (HaisfieldWolfe et al, 2009). Findings in this study indicated more depression cases than obtained in an earlier study done in Hong Kong (Rajandram et al, 2011). Rajandram et al (2011) concluded that approximately 8% of the oral cancer study participants met the clinical cut-off for depression.…”
Section: Discussioncontrasting
confidence: 56%
“…Findings in this study indicated more depression cases than obtained in an earlier study done in Hong Kong (Rajandram et al, 2011). Rajandram et al (2011) concluded that approximately 8% of the oral cancer study participants met the clinical cut-off for depression. This difference may be due to time since treatment completion.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The median of 90 is a high value of KPS when compared to that of cancer patients with pain from a Norwegian study, which obtained an average of 64.9% (± 15.6) (23) . Anxiety and depression have been identified as common psychological distress factors in most cancer patients (10) . The group that had decreased hope presented an increase in the depression score, which favors evaluating hope as a positive way in coping with the disease (1) .…”
Section: Discussionmentioning
confidence: 99%
“…Coping: Literature associates hope as an important resource and coping mechanism (1) . Anxiety and depression: Hope and optimism are negatively correlated to anxiety and depression (10)(11) . The higher the hope scores, the lower the possibility of the patient presenting a score of depression (5)(6) .…”
Section: Introductionmentioning
confidence: 99%